CAUSE CATEGORY DAN PRODUCT TYPE DAN RESPON KONSUMEN - Taufik Akbar (POLITEKNIK LP3I JAKARTA, 2014)
This thesis is discussing the effect of product type (the hedonistic products and the utilitarian products) and cause category (human services, health, animals and environmental protection) toward consumer responses in the cause-related marketing offers of the students LP31, Cikarang. It was a quantitative research by the experimental research design. The result showed that the hedonistic products gave a positive response than the utilitarian products in the cause-related marketing offers. Meanwhile, in the human services cause and health category got a better response rather than the animals and environmental protection cause category. However, in the category of health cause compared to animals cause, the participants' response was not significant. In term of interaction between the product type and the cause category, there was only the purchase intentions which affected significantly.Therefore, it is suggested to do the advanced research by using several hedonistic and utilitarian products. Whereas for cause category uses blind brand for reduce to effect of strength NGO brands. Keyword: Product Type, Cause Category , Cause-Related Marketing, Consumer Responses, Ads